Presence of antibodies against H5, H7 and H9 influenza a virus in wild birds in the state of São Paulo, Brazil - de Sousa, E. [UNESP]; Costa, T. P. [UNESP]; Werther, K. [UNESP]; Durigon, E. L.; de Araujo, J.; Ferreira, C. S.; Pinto, A. A. [UNESP] (FapUNIFESP (SciELO), 2013)
Although the natural reservoirs of the avian influenza (AI) virus have been extensively studied in many countries, there is a clear lack of information on this subject in South America, particularly in Brazil. The objective of this study was to conduct a serological survey for H5, H7 and H9 antibodies to AI-subtype viruses in wild birds in the state of São Paulo, Brazil. Serum samples were tested using the hemagglutination-inhibition assay. Out of the 31 wild birds sampled between January and December of 2006, seven (22.58%), were seropositive for H5, H7 and H9; four (12.90%) were seropositive for H5 and H7; 13 (41.94%), were seropositive only for H7; three (9.7%), were seropositive only for H9; and four (12.90%) were negative for all three hemagglutinin subtypes. These results indicate that AI viruses belonging to H5, H7 and H9 subtypes circulate among wild birds in the state of São Paulo in the form of either concurrent or consecutive infections. This study contributes to the knowledge of AI epidemiology in Brazil, and stresses the need of further detailed and long-term epidemiological and ecological investigation to determine the current status of this virus.
Keywords: Avian influenza virus; Brazil; Hemagglutina-tion inhibition; Reservoir; Wild bird